2021
DOI: 10.7150/ijbs.58876
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of LRRC4C in Colon and Gastric Cancers correlates with Tumour Microenvironment Immunity

Abstract: In this study, we aimed to use ESTIMATE and CIBERSORT computational methods to analyse transcriptional information on COAD and STAD in TCGA. We downloaded transcriptome RNA-seq data of 446 patients with colon cancer from TCGA and estimated the amount of immune and stromal components in the COAD samples using CIBERSORT algorithms. We analysed differentially expressed genes in 446 TCGA samples and 585 Series GSE39582 samples, in high- and low-scoring groups, using Cox regression. The expression of LR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…While the majority of the 567 SNP-based patient subgroups indeed were associated with no clinical outcome differences as a function of SNP genotype, ∼1% of SNP-based patient subgroups did have an association with either three or four of the four key clinical outcomes assessed. The majority of the SNPs were not associated with any known gene; the few genes that have been studied were in associated with cancers of various tissues ( lrrc4c 43 and linc01317 44 ), xenophagy of bacteria and viruses ( sacm1l 45 ), Ca 2+ channels on endothelial cells ( trpc4 46 ), as well as neuronal dysfunction ( lrrc4c 47 , 48 and slc20a2 49 ). Further study is needed to determine if and how these genes (or SNPs in linkage disequilibrium with these particular SNPs) might be associated with organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…While the majority of the 567 SNP-based patient subgroups indeed were associated with no clinical outcome differences as a function of SNP genotype, ∼1% of SNP-based patient subgroups did have an association with either three or four of the four key clinical outcomes assessed. The majority of the SNPs were not associated with any known gene; the few genes that have been studied were in associated with cancers of various tissues ( lrrc4c 43 and linc01317 44 ), xenophagy of bacteria and viruses ( sacm1l 45 ), Ca 2+ channels on endothelial cells ( trpc4 46 ), as well as neuronal dysfunction ( lrrc4c 47 , 48 and slc20a2 49 ). Further study is needed to determine if and how these genes (or SNPs in linkage disequilibrium with these particular SNPs) might be associated with organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Applying the CIBERSORT algorithm to analyze the immune infiltration of tumor tissues in the TCGA database, the infiltration scores of various immune cells in renal clear cell carcinoma were obtained, and the immune cell types related to prognosis were obtained. Moreover, the infiltration scores of immune cells in other tissues, such as head and neck squamous cell carcinoma, gastric cancer, and other tumors [ 29 31 ]. Particularly the infiltration of M2 macrophages was studied about tumor growth and invasion; this provides a reference for our research [ 32 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that ceRNA regulatory network is related to the tumor immune microenvironment ( 51 ), and various RNAs are also related to tumor immunity ( 52 54 ). Through the correlation analysis of the two, we found similar conclusions.…”
Section: Discussionmentioning
confidence: 99%